The impact of socioeconomic deprivation on liver transplantation - De Simone, Paolo; Germani, Giacomo; Lai, Quirino; Ducci, Juri; Russo, Francesco Paolo; Gitto, Stefano; Burra, Patrizia (Frontiers in Transplantation, 2024)
Despite global expansion, social disparities impact all phases of liver transplantation, from patient referral to post-transplant care. In pediatric populations, socioeconomic deprivation is associated with delayed referral, higher waitlist mortality, and reduced access to living donor transplantation. Children from socially deprived communities are twice as much less adherent to immunosuppression and have up to a 32% increased incidence of graft failure.Similarly, adult patients from deprived areas and racial minorities have a higher risk of not initiating the transplant evaluation, lower rates of waitlisting, and a 6% higher risk of not being transplanted. Social deprivation is racially segregated, and Black recipients have an increased risk of post-transplant mortality by up to 21%. The mechanisms linking social deprivation to inferior outcomes are not entirely elucidated, and powered studies are still lacking. We offer a review of the most recent evidence linking social deprivation and postliver transplant outcomes in pediatric and adult populations, as well as a literature-derived theoretical background model for future research on this topic.